A cross-sectional study of self-reported dietary supplement use, associated factors, and adverse events among young adults in Kuwait - Dana AlTarrah; Zahraa ElSamra; Wahibe Daher; Alanood AlKhas; Lolwah Alzafiri (BMC, 2024)
Abstract Background Dietary supplements (DS) are commonly used to improve overall health status and correct nutritional deficiencies. However, with the global rise in DS use, there is an increased risk of misuse and/or excessive use leading to toxicity and adverse events (AE). Research on DS use and DS-related AE is limited in Kuwait. This study aimed to explore the prevalence of DS use, its associated factors, and reported AE in a population of young adults. Methods A cross-sectional study was carried out using an online self-administered questionnaire. Non-probabilistic sampling was used via multiple social media platforms. Logistic regression analysis was performed to assess the association between sociodemographic, lifestyle characteristics and health status with DS use and AE. Results The prevalence of DS use was 68.24%. DS use was found to be associated with age (odds ratio [OR] = 1.07, 95% confidence interval [CI] 1.03-1.13; p-value [p] = < 0.001) and being female (OR = 1.55, 95% CI 1.01-2.41; p = 0.047). AE related to DS use were found to be associated with having respiratory disorders (asthma) (OR = 2.09, 95% CI 1.07-4.05; p = 0.029) and digestive disorders (OR = 3.22, 95% CI 1.24-8.35; p = 0.016). Conclusion The study findings provide valuable insights into current DS use in young adults in Kuwait, which may enable the strategic development of targeted interventions and health promotion awareness campaigns. Furthermore, they emphasize the necessity of implementing regulations and policies to effectively manage DS use and monitor AE reporting in Kuwait.